DEVELOPING SIMPLE PRESENT TENSE MASTERY IN WRITING DESCRIPTIVE TEXT AT THE FIRST SEMESTER STUDENTS OF STISIP PERSADA BUNDA PEKANBARU - Lia Diana (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
The simple present tense is the most basic tense that should be mastered by the first semester students of STISIP Persada Bunda Pekanbaru. Moreover, descriptive text is one of the text types which use the present tense. Descriptive text is used by the researcher as the text that let the students apply their ability in using the present tense. However, most students still face difficulties in using present tense in writing descriptive text. Thus, the researcher conducted the study entitled